Legislação em disputa: o caso da lei paulista de combate à discriminação por orientação sexual - Polato, Murilo Bernardino (2020)
This dissertation aims to carry out a case study on the law 10.948/01 of the State of São Paulo, which presents itself as legislation that combats discriminatory acts committed to LGBT people. For this, the various constructions of mobilizations of this cause by the activists are analyzed, being these in the form of protests or by institutional means, seeking to relate their speeches and the forms of mobilization with the search for deputies who help them to project their demands in policies public. In addition, we analyze the context of the Legislative Assembly of the State of São Paulo and how was the presentation, discussion, and approval of this bill that in the future became this legislation. The work has as references the fields of citizenship, social movements, public and legislative policies. And, for its complete realization, semi-structured interviews combined with important documents to the case study were used as data collection forms.